Stabilities of modulated phases of close packed materials - Ahmad, S.; Khan, M.A. (Wiley, 2000)
The one-dimensional Ising model has been used to study polytypism in close packed materials. The spin assignment criterion so far employed has been shown to be inappropriate and an alternative to this was developed. Relative cohesive energies and the phase diagrams have been worked out using this criterion. The new procedure modifies the results significantly. Simulation of polytypes was carried out in presence of screw and edge dislocations as well as in their absence.